THE DEVELOPMENT OF ACCOUNTING LEARNING MEDIA USING LECTORA INSPIRE IN FINANCIAL STATEMENT TOPIC OF GRADE X AT SMK NEGERI 1 MALANG - Saadah, Nur Laili; Mentari, Sriyani; Juliardi, Dodik (Journal of Accounting and Business Education, 2016)
The aim of developing instructional media by using lectora inspire is to produce interactive instructional media and the effectiveness on the topic of financial statement of service and trading company tenth grade at SMK Negeri 1 Malang. The development of instructional media which refers to the steps of research and development by Borg & Gall (1983) modified with Sadiman (2010) which are: 1) research and information collecting, 2) planning, 3) develop preliminary form of product, 4) production media, 5) expert validation, 6) revision of the product, 7) field trials, 8) revision of the results of field trials of products, 9) final product. The technique of data analysis in this research is using qualitative descriptive analysis and assumption test by using T-test independent sample. The method of development used is by experimenting the product. The final product of this study has overtaken the expert validation which result 80,46% valid in terms of materials given, 89,28% valid in terms of media, and 96,30% valid based on the result of the field trials, so that it was averaged 88,68% valid from the validation results. The result of T-Test independent sample acquired a significant result 0,015 < 0,05 so that can be concluded that there was a significant distinction on the improvement of studentsâ learning outcomes in the experimental and control class.Keywords: developing instructional media, lectora inspire, financial statement.